Pengaruh Kepemimpinan Transformasional, Motivasi terhadap Kepuasan Kerja Karyawan pada Perusahaan Manufaktur di Kota Batam - Adi Neka Fatyandri; Lylya Shanty (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
Transformational Leadership is a leadership style that prioritizes employee welfare, motivates and inspires them. Based on data obtained from the Central Statistics Agency, the Open Unemployment Rate in Batam City has increased by 1.78 points when compared to the TPT in August 2020 of 37.69%. This study aims to determine the effect of transformational leadership, motivation on employee job satisfaction in manufacturing companies in Batam City. This research was conducted with a survey method distributing questionnaires to 211 respondents who are employees who work at the three large-scale PT Manufaktur in Batam City, namely PT. Satnusa Persada, Tbk, PT. Philips Industries Batam, PT. Siix Electronic Indonesia. Then the data obtained were tested with SPSS and Smart PLS. From the test results, it can be concluded that transformational leadership has an effect on job satisfaction. Meanwhile, inspirational motivation has no effect on job satisfaction.